Thiol-ene-based degradable 3D printed network from bio resource derived monomers ethyl-lactate and isosorbide - Pal, Shibam; Asha, S. K. (European Polymer Journal, 2024)
A polymeric ene-based thiol-ene network is reported that was demonstrated for light-based 3D printing. Allyl poly (acrylate ethyl lactate) (PAEL) was synthesized starting from ethyl lactate in an efficient and scalable manner. Ethyl lactate is a biobased material obtained naturally or chemically in high yields in the form of ethyl ester of lactic acid. Isosorbide, which is also a bio based resource was converted into thiol derivative and was used along with Pentaerythritol tetrakis(3-mercaptopropionate) (PETMP) as multifunctional thiol. The polymeric nature of the ene (i.e. PAEL) imparted exceptionally high mechanical properties like Young's modulus of 1.75 GPa as well as high thermal stability with a decomposition temperature (Td,10%) exceeding 350 C for all the networks studied. The properties could also be customized by fine tuning the type and stoichiometric ratio of the thiol crosslinked employed. For instance, the Young's modulus range from 1.75 GPa to 1.03 GPa and glass transition temperature range from 44 C to 54 C could be achieved. DLP 3D printing was used to demonstrate the printability of the resins with high resolution and structural fidelity. The study also highlights the basemediated rapid hydrolytic degradation efficiency of the 3D printed parts, demonstrating the applicability of these novel polymeric ene based thiol-ene for sustainable and eco-friendly 3D printable formulations.
Keywords: 3D printing; Degradation; digital light processing; Poly (acrylate ethyl lactate); Thiol-ene